Resor Kampung Nelayan Berdasarkan Pendakatan Arsitektur Hijau Dengan Standar GBCI - S, Mira D; W, Ari; H, Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Resor Kampung Nelayan, with theme green architectural is the title of the last design or thesis that take location in the coast area Batam Archipelago. Exactly in the chief of village Sembulang, Rempang Island, Batam Archipelago. Resort is a place to stay that identical to nature, which has special facilities to relaxing activity and sports such as swimming, spa, tracking, and jogging. Green architectural is an architecture that use minimum consumption of natural resources, include energy, water, and material, also minimum in caused negative effect to the environment. Chief of village Sembulang is a chief of village that has enough potential in beach area, but still not yet get development in tourism sector. Because of that, adding resort as one of tour destination that wished can maximize that potential. With the title of Resort Kampung Nelayan, it meant this resort will be presenting villages or fisherman community as an icon of the resort. The problem that we get in this design is how to match the natural potential, resort, tour, and community in one design. The purpose that want to be reached is that the design can be mixed with nature dan also kind to the environment to maximize the potential which is exist, so that tour and resort that are available can be served maximally. So resort design with green architectural theme is a design that kind to the environment around and can give comfortable atmosphere for users because a resort must match with the conditional around and can give comfortable feels.Keywords: Resort, Green Architectural, Fisherman Community.